2021
DOI: 10.3390/ma14174803
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Spatial Anisotropy of the Surface MicroStructures of Different Implant Materials: An Atomic Force Microscopy Study

Abstract: Many biomaterials’ surfaces exhibit directional properties, i.e., possess spatial anisotropy on a range of spatial scales spanning from the domain of the naked eye to the sub-micrometer level. Spatial anisotropy of surface can influence the mechanical, physicochemical, and morphological characteristics of the biomaterial, thus affecting its functional behavior in relation, for example, to the host tissue response in regenerative processes, or to the efficacy of spatially organized surface patterns in avoiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…As a result, indentation becomes an irreversible process, or, in other words, residual indent is found on the sample, and elastic–plastic deformation regime should be assumed to fit the data [ 38 ]. In our work, the usage of nanometrically sharp tips for better spatial resolution implies h ~ R , therefore the modified Hertz model of Section 2.2 can be used to fit the data [ 41 , 42 , 43 ]. This allowed to numerically process nanometric indentations into PEEK, while the usage of low-stiffness cantilevers allows investigating the polymer mechanical response to small applied forces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, indentation becomes an irreversible process, or, in other words, residual indent is found on the sample, and elastic–plastic deformation regime should be assumed to fit the data [ 38 ]. In our work, the usage of nanometrically sharp tips for better spatial resolution implies h ~ R , therefore the modified Hertz model of Section 2.2 can be used to fit the data [ 41 , 42 , 43 ]. This allowed to numerically process nanometric indentations into PEEK, while the usage of low-stiffness cantilevers allows investigating the polymer mechanical response to small applied forces.…”
Section: Discussionmentioning
confidence: 99%
“…The PEEK samples were medical-grade sheets (10 × 10 × 6 mm height; Direct Plastics Ltd., Sheffield, UK) with semimachined surfaces, as described previously [ 43 ]. AFM measurements were performed by a NT-MDT (Moscow, Russia) system equipped with an upright optical microscope.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface of porous polystyrene films produced with 50% PS/50% PBMA presents the highest degree of isotropy, 90.34%; followed by the 40/60 weight ratio with the isotropy degree of 77.54%, a surface is isotropic if it presents identical characteristics regardless of the measurement direction, such as the case of surfaces with a random surface texture without any texture that stands out. Gambardella et al [ 33 ] found that anisotropy tends to decrease towards small length scales because downscaling gives way to smaller features contributing to the distribution of asperities within the topography. For films formed with a 40/60 weight ratio, the polar spectrum shows the angles for the first direction (90°), second direction (63.49°), and third direction (33.72°), and the privileged texture direction corresponds to 90°.…”
Section: Resultsmentioning
confidence: 99%